Understanding the Management of Nanomaterials Safety in Research Environment - Wedad H. Al-Dahhan; Khalid Zainulabdeen; Atheel Alwash; Emad Yousif; Salam Mohammed (Fakultas Teknik, 2022)
The concept of safety is as ancient as the history of humankind. However, as civilization progressed, this concept has showed a new dimension. Nanomaterials, the particle with diameters less than 100 nanometers (0.1 micrometers), is commonly benefitted nowadays. The use of these materials or technology has a great impact on the progress of industry, agriculture, and the advancement of scientific research. Its applications also have a direct impact to people's lives. Many researchers show interest in the unique properties of nanomaterials, ignoring the safety measures that should be taken when handling with these materials. This paper presents the main and important procedures need to be measured when dealing with nanomaterials, starting from the definition of the properties of these materials supported by some other examples. The research also highlights the roots of exposure to these materials and the personal protective equipment that should be used and how their waste can be disposed.